Analysis of the functionality of voice and video communication systems - Piątkowska, Aleksandra (Journal of Computer Sciences Institute, 2022)
The article contains a comparison of the functionality and qualitative verification of voice and video communication systems, through tests of voice message shift in time, at different data rates, tests of system use cases and the study of the popularity of applications in various environments and age groups, thanks to an electronic survey . The systems examined were: Microsoft Teams, Zoom, Signal, WhatsApp, Cisco Webex Meetings. The following hypothesis was made: Voice and video communication systems are very popular systems among users, and their functional capabilities are similar.